2016
DOI: 10.1074/jbc.m115.691352
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 Regulates the Function of Mitochondrial Permeability Transition Pore by Targeting VDAC1 Expression

Abstract: Mitochondrial dysfunction is one of the major contributors to neurodegenerative disorders including Parkinson disease. The mitochondrial permeability transition pore is a protein complex located on the mitochondrial membrane. Under cellular stress, the pore opens, increasing the release of proapoptotic proteins, and ultimately resulting in cell death. MicroRNA-7 (miR-7) is a small non-coding RNA that has been found to exhibit a protective role in the cellular models of Parkinson disease. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 39 publications
5
74
1
1
Order By: Relevance
“…Chaudhuri et al. (Chaudhuri et al , 2016) demonstrated in neuroblastoma SH-SY5Y cells that knockdown of VDAC1 decreased ROS production and injury from complex-1 inhibition, indicating that VDAC1 directly contributes to neuronal cell death secondary to depletion of ATP. However Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chaudhuri et al. (Chaudhuri et al , 2016) demonstrated in neuroblastoma SH-SY5Y cells that knockdown of VDAC1 decreased ROS production and injury from complex-1 inhibition, indicating that VDAC1 directly contributes to neuronal cell death secondary to depletion of ATP. However Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reduction of miR-7 could play an important role in PD neurodegeneration through these two different mechanisms. However, a recent study has showed that miR-7 regulates the function of mitochondrial permeability transition pore by repressing VDAC1 expression [164], suggesting a potential role of this miR in preventing mitochondrial dysfunction. Hence, it will be important to determine the levels of miR-7 in PD patients in order to understanding how it can be dysregulated during the progression of the disease.…”
Section: Nrf2 and Mirnas In Parkinson's Diseasementioning
confidence: 99%
“…Similarly knockdown of VDAC1 also led to a decrease in intracellular ROS production and subsequent cellular protection against MPP +. Thus, the protective effect of miR-7 is partly influenced through provoking mitochondrial function by targeting VDAC1 expression [187]. Further, a Parkin-AMPK alliance has recently been reported to be involved in neuroprotection against mitochondrial dysfunction.…”
Section: Methazolamide (Mtz)mentioning
confidence: 99%